Bioactivity of Ethanolic Extract of Propolis (EEP) in Balb/C Mice's CD4+CD25+ and B220+ Lymphocyte Cells - Aden, Aisyah Zahroh; Rifa'i, Muhaimin (The Journal of Experimental Life Science, 2014)
This experiment was aimed to determine the bioactivity of ethanolic extract of propolis (EEP) against the changes in the quantity of CD4+CD25+ and B220+ lymphocytes and determine the optimal dose of EEP to increase the number of CD4+CD25+ and B220+ cells in Balb/c mice. Balb/c mice were divided into four treatment groups: control treatment, treatments of EEP at a dose of 50 mg.kg-1, 100 mg.kg-1, and 200 mg.kg-1 body weight of mice. All mice were dissected after two weeks post treatment. Profiles of lymphocytes from the spleen expressing CD4+CD25+ and B220+ cells were analyzed by flowcytometry using CellQuest software. Data was analyzed by Kruskall Wallis and Mann Whitney statistical test with P<0.05 using SPSS 16.0 for Windows. The results showed that the treatment of dose of 50 mg.kg-1 of EEP can increase relative number of CD4+CD25+ cells significantly, but those cells decrease significantly when we apply the dose of 100 and 200 mg.kg-1. The relative number of B220+ cells increase in the dose of 50 and 200 mg.kg-1 and decrease in the dose of 100 mg.kg-1 compared to the control. This experiment suggest that EEP has bioactivity to modulate the quantity of CD4+CD25+ and B220+ in dependent manner.Keywords: B220+, CD4+CD25+, lymphocyte, propolis